The Implication of Business Digitalization, Organizational Learning, and Innovation Capabilities on the Firm Performance of MSMEs - Ningsih, Ayu; Priscilla, Lysandra; Kaltum, Umi (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2024)
Background – In recent years, more businesses have been adopting digital technologies to streamline processes, enhance customer experiences, and stay competitive. The COVID-19 pandemic has accelerated this digital transformation, creating opportunities and challenges for MSMEs in Bandung, Indonesia. As MSMEs contribute significantly to employment and economic growth, they face obstacles in adapting to changing conditions in the technological and disrupted market landscape. Aim – This study examines the implications of Business Digitalization, Organizational Learning, and Innovation Capabilities on the Firm Performance of micro in Small, and Medium Enterprises (MSMEs). Design/ Methodology/ Approach – This research study was conducted in the City of Bandung, Indonesia, and collected survey data from 129 MSMEs that have undergone digital transformation. Non-probability sampling was employed in the study. The relationship between business digitalization, organizational learning, innovation capabilities, and firm performance was analyzed using SPSS software through multiple regression analysis. Findings – The findings reveal that business digitalization significantly enhances firm performance by facilitating knowledge creation, collaboration, and operational efficiency for MSMEs. Organizational learning has a considerable positive influence on firm performance, improving decision-making, promoting innovation, and enabling successful adaptation. Similarly, innovation capabilities positively influence firm performance by driving the development of new products, cost-cutting measures, and differentiation. Conclusion - MSMEs in developing their businesses are advised to use digital bases and develop innovative innovations Research implication – this research contributes to the field of management studies by shedding light on the interconnectedness of business digitalization, organizational learning, innovation capabilities, and firm performance in the context of MSMEs. The findings provide actionable insights that can guide MSMEs towards improved strategies for success in a rapidly evolving business landscape Limitations – This study focuses on MSMEs that have digitized their business and have undertaken organizational learning and innovation capabilities. From the time of the pandemic 2019 until 2023, without excluding other potential factors that may affect firm performance among MSMEs, such as market competition and external environmental factors.